Fabrication and characterization of copper oxide thin film by thermal CVD for ethanol sensor application - Lim, Hui Teng (2017)
A gas sensor is a device used to warn us of dangerous gases Gas sensors based on metal oxides semiconductors are important devices in modern technologies. Gas sensors play critical roles in many fields such as industrial production, environmental pollution, and traffic safety. Cupric oxide (CuO) thin films were prepared on a glass and FTO substrates by thermal CVD method. The substrate, deposition temperature, oxygen flow rate, and substrate were varying during deposition. The morphological, optical and electrical properties of CuO films were characterized by FE-SEM, atomic force microscopy (AFM), ultra-violet visible spectrophotometer, respectively, two point probe techniques and Keithley system. The FE-SEM result showed that spherical and uniform shaped were obtained on a glass substrate while the porous structure was obtained on FTO. AFM showed well organized morphology with the highest root mean square surface roughness for CuO thin films on glass and FTO substrates were 23 and 27nm, respectively. The optical direct band gap energy of the CuO film grown on glass and FTO substrate were in the range 1.8-l.86eV. The current-voltage characteristic has been formed with the threshold voltage (V th) of 2V and breakdown voltage (Vs) of -SV. The highest value of resistance was obtained which is 6.99xl06 0 when the CuO sensing element is contacted with to ethanol liquid. This work has successfully demonstrated the formation of optimized copper oxide thin films and for ethanol sensing application.